Female Creativity in Organizations: What is the Impact of Team Composition in Terms of Gender during Ideation Processes? - PARMENTIER, Guy; LE LOARNE-LEMAIRE, Séverine; BELKHOUJA, Mustapha (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
This paper questions the impact of team gender composition on idea generation and idea evaluation? Based on econometric analyses of evaluations of 100 product ideas proposed by 463 students, it shows that ideas supported by teams mostly composed of either males or females are as creative as ideas supported by mixed teams when they are evaluated by experts. When these ideas are evaluated by peers, the ideas supported by mixed teams are perceived as being less creative than ideas supported by teams that are predominantly composed of either males or females.